Advances in the Synthesis of Spirocyclic Nucleosides - Kumar, Sumit; Khan, Yousuf; Arora, Aditi; Kumar, Manish; Rungta, Pallavi; Singh, Brajendra K.; Sharma, Vivek K.; Singh, Sunil K. (Synthesis, 2023)
The nucleosides are the building blocks for nucleic acids and composed of a five-carbon sugar bearing either pyrimidine or purine nucleobase. The biological properties of nucleosides can be tailored by chemically modifying the five-carbon sugar to influence its sugar pucker. The spirocyclic scaffold is an indispensable scaffold in more than ten approved drugs, and its inherent three-dimensionality makes it an ideal modification to influence the sugar pucker and biological properties of nucleosides. However, the introduction of spirocyclic scaffold is often synthetically challenging due to increase in synthetic steps and stereocenters. The present review highlights the advances in synthetic methodologies developed during the past decades for accessing various members of the spiro-functionalized nucleoside family.1 Introduction2 C-1′-Spirocyclic Nucleosides3 C-2′-Spirocyclic Nucleosides4 C-3′-Spirocyclic Nucleosides5 C-4′-Spirocyclic Nucleosides6 Miscellaneous Spirocyclic Nucleosides7 Conclusion and Future Perspectives
Keywords: sugar-modified nucleoside; hydantocidin; spironucleoside; spirocyclic scaffold; Vorbrüggen glycosylation; chemoenzymatic synthesis